TIME CONSTANT FOR EQUILIBRATION OF EROSION WITH TECTONIC UPLIFT - Hooke R.L. (My University, 2003)
Following a change in the rate of convergence in a collision zone, the rate of rock uplift also changes. This results in a change in relief, and hence in erosion rate. Thus, over time, the erosion rate tends to adjust to equal the rock-uplift rate. A perturbation analysis of a mountain mass at critical taper suggests that the time constant for this adjustment varies from 105 to >108 yr, depending on initial relief, lithology, and erosion law. Under most conditions, time constants for the adjustment are long enough to preclude attainment of a steady state during a typical orogeny lasting on the order of 107 yr. However, if erosion increases exponentially with relief, a close approach to a steady state is possible in the relatively few mountain belts on Earth with exceptional relief and/or weak lithologies. [PUBLICATION ABSTRACT]
Keywords: mountains; erosion; response time; tectonic geomorphology